2018
DOI: 10.1021/acsami.8b17479
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Functionalized Metal–Organic Frameworks and Covalent Organic Polymers as Potential Sorbents for Removal of Formaldehyde in Aqueous Phase: Experimental Versus Theoretical Study

Abstract: Porous materials have been identified as efficient sorbent media to remove volatile organic compounds. To evaluate their potential as adsorbents, the adsorptive removal of formaldehyde (FA) in aqueous environments was investigated using four materials, two water-stable metal− organic frameworks (MOFs) of UiO-66 (U6) and U6-NH 2 (U6N) and two covalent organic polymers (COPs) with amine-functionality, CBAP-1-EDA (CE) and CBAP-1-DETA (CD). U6N exhibited the highest removal capacity of 93% (0.56 mg g −1 ) of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 59 publications
4
56
0
Order By: Relevance
“…The diversity of the metal centers and organic ligands leads to materials of particular crystallographic structure, texture, and chemistry. Due to these properties, MOFs have been tested for various applications such as gas separation/storage [4][5][6][7][8][9], purification [10][11][12], sensing [13][14][15][16], electrodes for batteries [17,18], microextraction [19,20], detoxification of chemical warfare agents [21][22][23][24][25], and heterogeneous catalysis [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the metal centers and organic ligands leads to materials of particular crystallographic structure, texture, and chemistry. Due to these properties, MOFs have been tested for various applications such as gas separation/storage [4][5][6][7][8][9], purification [10][11][12], sensing [13][14][15][16], electrodes for batteries [17,18], microextraction [19,20], detoxification of chemical warfare agents [21][22][23][24][25], and heterogeneous catalysis [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Under most conditions, it was found that all three models had high regression coefficients (R 2 ), suggesting a mixed process of single-and multi-layer adsorption. The results further implied a multi-interaction-driven adsorption process [41], in which electrostatic attraction (single-layer), π-π interaction (multi-layer) and/or H-bonding (either single-or multi-layer) occurs [42].…”
Section: Adsorption Mechanismmentioning
confidence: 88%
“…These findings suggest that the HKUST-1^UiO-66 granules would be efficient for the removal of formaldehyde from the air, as formaldehyde is a sticky compound even at ambient temperature and pressure conditions owing to its strong interaction with adsorbents (43,44). Formaldehyde is an environmentally harmful gas existing in trace amounts in the air (45)(46)(47)(48), and MOFs are promising absorbents for efficiently removing it from the air (49)(50)(51)(52)(53)(54). The formaldehyde removal capacities of the samples were tested using a specially designed process, as shown in Figure 3(a).…”
Section: Heterojunction Of Pores In Granola-type Crystalsmentioning
confidence: 99%